Lead Metal Adsorption from its Solution using Seagrass Biomass Enhalus Acoroides - Siti Masita; Irwan Said; Suherman Suherman (Universitas Tadulako, 2020)
Seagrass is one of the macrophyta plants containing enough biomass. Recently, seagrass has been used for filtering waste, drugs and sources of chemicals. Seagrass also functions to stabilize the soft bases where most species grow, especially with solid root systems and cross each other. Therefore, seagrass has the potential to absorb heavy metal ions from the solution. This research aimed to determine the optimum weight and optimum contact time for Pb metal adsorption. Weight variation of seagrass biomass was 60, 90, and 120 mg while variation in contact time was 60, 90, and 120 minutes. The results obtained optimum weight of seagrass biomass to absorb Pb metal was 60 mg with 98.42% Pb absorbed, and optimum contact time for seagrass biomass to absorb Pb metal was 60 minutes with 95.45% Pb absorbed.